Ilmu dan Teori-Teori Kebenaran, dan Kontekstualisasinya dengan Pendidikan Islam - Koto, Eldawati; Wahab, Muhbib Abdul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In this academic writing, there are three main discussions. The first discussion is about whether knowledge comes solely from reason ('aqliyyah). Next, the second discussion focuses on whether the "truth" of knowledge can be described with correspondence, coherence, practical-pragmatic, performative, consensus, and religion as theories of truth. The final discussion is about the source of knowledge, the process, and methods to obtain knowledge, ways to prove the truth of knowledge, and the levels of truth of knowledge. The level of truth of contextual knowledge in Islamic education comes from the revelation of Allah SWT, namely the Al-Qur'an. This academic writing is created to explore the position of knowledge and truth, as well as the nature and source of knowledge, and truth in the view of Islamic Education Science with the source of the Al-Qur'an.